Division Tenorrhaphy: A Novel Technique for Chronic or Failed Nonoperatively Treated Achilles Tendon Rupture. Issue 3 (June 2017) - Doty, Jesse; Katsuura, Yoshihiro; Richardson, Nicholas
Here we describe a modified open technique for the repair of a ruptured Achilles tendon using multiple looped sutures with the creation of interdigitating tendon stumps maximizing surface area for suture application as well as allowing for significant tissue overlay. This technique produces a high strength repair that is useful in cases of extensive degeneration or poor-quality tissue. Degenerative tissue may be encountered with chronic ruptures or failed nonoperative treatment, as well as those ruptures that occur at the proximal myotendinous junction. We present 2 cases in which the technique was utilized: one of a failed nonoperatively treated rupture and another of a chronic rupture. The technique was found to be successful for both patients with improvement in visual analogue scale, Achilles tendon total rupture score, American Orthopaedic Foot and Ankle Score, and Foot and Ankle Disability Index. Levels of Evidence: Level IV